B vitamins intake and cognitive status of elderly in Kuantan, Pahang - Lokman, Nur Fatin Atiqah; Hamirudin, Aliza Haslinda (2018)
The number of elderly whom diagnosed with cognitive impairment are increasing in Malaysia and becoming a matter of a great concern for the health sectors. One of the ways to overcome this rising problem is by modifying risk factor which in this case, dietary intake particularly by consuming diet rich in B vitamins (folate, vitamin B12 and B6). This study aimed to identify total B vitamins intake, cognitive status and the associations between both total B vitamins intake and cognitive status of elderly in Kuantan, Pahang. Seventy-eight subjects of elderly aged ≥60 years old were recruited in this study. All eligible subjects were invited to participate in the study and home visits have been done. All subjects were recruited through convenience sampling method. Subjects were interviewed using a questionnaire on their demographic data. Dietary history method was used to collect information on dietary intake; whilst the cognitive status was assessed using the Malay version of Mini Mental State Examination (MMSE). Dietary intake was analyzed using Nutritionist Pro Software version 3.00. From the findings, most of the subjects have inadequate total folate (93.6%)and vitamin B6 (92%) intake. Meanwhile, 63% achieved adequate total vitamin B12 intake. The total B vitamins intake data were compared with Malaysian's Recommended Nutrient Intake (RNI, 2017). All results were statistically significant (p-value < 0.05) except for total vitamin B12 intake's result (p-value > 0.05). Besides, most of the subjects have normal cognitive function as 62.8% of them achieve normal MMSE score (>24 out of 30 marks). The correlation between B vitamins intake and cognitive status of the elderly in Kuantan, Pahang were found to be weak and not statistically significant. Emphasis on the importance of adequate nutrients intake needs to be taken place to ensure optimum nutritional status and health condition among the elderly.